HUBUNGAN PENGGUNAAN ARTIFICAL INTELLIGENCE DALAM PEMBELAJARAN DENGAN HASIL BELAJAR MAHASISWA PGSD FIP UNM - Irmawaty, A.; Hidayatullah, Ryan; Hikmah Damayanti, Nurul; Faisal, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the relationship between the use of Artificial Intelligence in learning and student learning outcomes in the Primary School Teacher Education Program, Faculty of Education, Universitas Negeri Makassar. This research used a quantitative approach with a correlational method. The sample consisted of 25 students from class M24.2 selected using purposive sampling. Data on the use of Artificial Intelligence were collected through a Likert-scale questionnaire, while learning outcomes were obtained from students' Grade Point Average. The validity test showed that all items were valid with correlation values ranging from 0.41 to 0.58. The reliability test produced a Cronbach’s Alpha value of 0.992, indicating very high internal consistency. The Shapiro-Wilk normality test showed that the data were not normally distributed with a significance value of 0.015, so the analysis was continued using Spearman correlation. The results showed a correlation coefficient of -0.198 with a significance value of 0.343. These findings indicate that there is no significant relationship between the use of Artificial Intelligence in learning and student learning outcomes. This result suggests that the use of Artificial Intelligence is not a dominant factor influencing student achievement and that other factors such as learning motivation and study strategies may play a more important role.